2018
DOI: 10.1021/acs.est.8b00838
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Phthalate Metabolites between Paired Maternal–Fetal Samples

Abstract: Phthalic acid esters (PAEs) are readily metabolized to phthalate metabolites (mPAEs) in the human body. The occurrence of mPAEs in adult human samples is well documented; however, the maternal-fetal transmission of mPAEs has seldom been studied. In this study, 78 paired maternal-fetal samples, including maternal urine (MU), maternal serum (MS), cord serum (CS), and amniotic fluid (AF), were collected from pregnant women in Tianjin, China. Seven mPAEs were detected in MS, CS, and AF, whereas all 11 investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 60 publications
4
31
0
Order By: Relevance
“…MnBP was the most common metabolite detected in our participants, followed by MiBP, MEP, MECPP, MEOHP, MEHHP, and MEHP. The pattern of phthalate exposure in the present study was similar to that noted in previous studies of pregnant women in Mainland China [39,40]. However, compared with the women in the NHANES 2011–2012 study, as well as the recent study of pregnant women in Charleston, US, the GM of MEP levels in the present study (6.33 ng/mL) was almost six- to eight-fold lower (37.7 ng/mL and 47 ng/mL, respectively) [30,41].…”
Section: Discussionsupporting
confidence: 91%
“…MnBP was the most common metabolite detected in our participants, followed by MiBP, MEP, MECPP, MEOHP, MEHHP, and MEHP. The pattern of phthalate exposure in the present study was similar to that noted in previous studies of pregnant women in Mainland China [39,40]. However, compared with the women in the NHANES 2011–2012 study, as well as the recent study of pregnant women in Charleston, US, the GM of MEP levels in the present study (6.33 ng/mL) was almost six- to eight-fold lower (37.7 ng/mL and 47 ng/mL, respectively) [30,41].…”
Section: Discussionsupporting
confidence: 91%
“…Mixtures consisting of 23 xenobiotic chemicals at several humanrelevant levels from already available biomonitoring data were prepared to mimic actual human exposure in the United States (CDC 2018;Frederiksen et al 2010;Högberg et al 2008;Kim et al 2015;Li et al 2015Li et al , 2017Li et al , 2018aNagayama et al 2000;Thomsen et al 2002;Wang et al 2015a;Xiao et al 2011;Zhao et al 2017). The MCF-7 cell was chosen as the experimental model because it is a sensitive hormone-responsive cell line (Levenson and Jordan 1997), and many selected chemicals have been previously reported to be xenoestrogens and EDCs.…”
Section: Experimental Workflowmentioning
confidence: 99%
“…concentrations were calculated by the average of all detected Max/ GM values from the year 1999 to 2016 (GM was replaced by 75th percentile concentration if below limit of quantification). The concentration of the remaining chemicals was calculated based on the sample size weighted Max/GM concentration from available biomonitoring studies (Frederiksen et al 2010;Högberg et al 2008;Kim et al 2015;Li et al 2015Li et al , 2017Li et al , 2018aNagayama et al 2000;Thomsen et al 2002;Wang et al 2015a;Xiao et al 2011;Zhao et al 2017). The single-compound stock solution was prepared in DMSO initially, and the stocks of chemicals in the mixture were pooled to create a solution that was 1,000 times each chemical's final concentration before dosing.…”
Section: Xenobiotic Mixture Selectionmentioning
confidence: 99%
“…[10,11] Several studies have shown that higher concentrations of urinary metabolites were found in women than in men [12], and pregnant women as well as fetuses, could be highly sensitive to the potential harmful effects of toxic metabolites of phthalates. [13,14] Phthalates can cross the placental barrier and have been measured in amniotic uid in studies on humans. [15,16] Furthermore, phthalates have potential immunomodulatory properties in animal models.…”
Section: Introductionmentioning
confidence: 99%